3D food printing: Controlling characteristics and improving technological effect during food processing. (June 2022) - Demei, Kong; Zhang, Min; Phuhongsung, Pattarapon; Mujumdar, Arun S.
Graphical abstract: Highlights: Advantages of 3D food printing are briefly introduced. Methods of controlling food materials' characteristics were summarized. Researches of post-processing to improve products quality were analyzed. Researches related to sterilization based on 3D printing is discussed. Abstract: 3D printing technology has a wide range of application in the food industry. Current research has focused on the improving printing accuracy and expanding the range of printing materials, while the feasibility of 3D printing technology in controlling processing characteristics and improving technological aspects have not yet been critically reviewed. This paper provides a concise critical evaluation of techniques to enhance the characteristics of 3D printed foods including their post-processing e.g. drying, frying, baking, cooling, sterilization etc. This paper provides guidance for future research and development in the field of post-treatment of 3D food printed products which is critically important for wider industrial application of this rapidly evolving technology.